Influence of selected hormones on pathogenesis of psoriasis - Baran, Anna; Flisiak, Iwona; Szterling-Jaworowska, Małgorzata; Chodynicka, Bożena (Dermatology Review/Przegląd Dermatologiczny, 2009)
Psoriasis is a chronic and recurrent skin disease, affecting 1.5-3% of the population. It is characterized by abnormal epidermal proliferation, immunological disturbances with predominance of Th1 response and complex pathogenesis. Among many factors inducing the disease, hormonal disturbances seem to be a very interesting, but still not well recognized problem. Based on current literature data, we evaluated the possible role of selected hormones: sex hormones, hypothalamic-pituitary-adrenal axis hormones, thyroid hormones, prolactin and growth hormone in the pathogenesis of psoriasis.